Catholic appropriations of the New School from Everardo Backheuser’s Pedagogical Manuals (1933 to 1946) (Práxis Educativa, 2021)
This paper aimed to analyze the Catholic appropriations of the New School, based on the pedagogical manuals written by Everardo Backheuser (1879-1951), from 1933 to 1946. Through the content analysis, according to Laurence Bardin, the main elements of the New School assimilated by the author, as well as his recommendations for the implementation of new pedagogical methods were identified and discussed. The results led to the conclusion that Backheuser presented a differentiated proposal for the New School, from his appropriations – as defined by Roger Chartier. By establishing a dialogue between the modern teaching proposal and the Church traditional recommendations in favor of the integral education, Backheuser contributed to the renovation of the Catholic Pedagogy in Brazil.Keywords: History of Education. Catholic Pedagogy. Brazil.